2014
DOI: 10.1088/1475-7516/2014/08/059
|View full text |Cite
|
Sign up to set email alerts
|

The observational status of Galileon gravity after Planck

Abstract: We use the latest CMB data from Planck, together with BAO measurements, to constrain the full parameter space of Galileon gravity. We constrain separately the three main branches of the theory known as the Cubic, Quartic and Quintic models, and find that all yield a very good fit to these data. Unlike in ΛCDM, the Galileon model constraints are compatible with local determinations of the Hubble parameter and predict nonzero neutrino masses at over 5σ significance. We also identify that the low-l part of the CM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
197
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(209 citation statements)
references
References 121 publications
(247 reference statements)
8
197
3
1
Order By: Relevance
“…Moreover, we do not believe that the distances might help to constrain such parameters: cosmological geometrical probes are generally very weak when used to compare ΛCDM (GR) with other alternative models; we have no observational errors on these distances which, thus, in principle, could re-scale in a completely free and un-physical way. Finally, in [13] it is shown that the Hubble function H(z) derived from their galileon model can differ from the expected ΛCDM behaviour for 5% in the redshift range covered by our data; a variation which is smaller than present observational errors and dispersion and, thus, still not detectable in a statistically valid way nowadays. It is worth to stress that results from [13] are obtained using only Planck CMB and some BAO data, which very likely pinpoint high redshifts regime behaviour quite well, but not equally well the lower one.…”
Section: B Gravitational Lensingcontrasting
confidence: 50%
See 1 more Smart Citation
“…Moreover, we do not believe that the distances might help to constrain such parameters: cosmological geometrical probes are generally very weak when used to compare ΛCDM (GR) with other alternative models; we have no observational errors on these distances which, thus, in principle, could re-scale in a completely free and un-physical way. Finally, in [13] it is shown that the Hubble function H(z) derived from their galileon model can differ from the expected ΛCDM behaviour for 5% in the redshift range covered by our data; a variation which is smaller than present observational errors and dispersion and, thus, still not detectable in a statistically valid way nowadays. It is worth to stress that results from [13] are obtained using only Planck CMB and some BAO data, which very likely pinpoint high redshifts regime behaviour quite well, but not equally well the lower one.…”
Section: B Gravitational Lensingcontrasting
confidence: 50%
“…Finally, in [13] it is shown that the Hubble function H(z) derived from their galileon model can differ from the expected ΛCDM behaviour for 5% in the redshift range covered by our data; a variation which is smaller than present observational errors and dispersion and, thus, still not detectable in a statistically valid way nowadays. It is worth to stress that results from [13] are obtained using only Planck CMB and some BAO data, which very likely pinpoint high redshifts regime behaviour quite well, but not equally well the lower one. The fit would have surely benefit (and maybe reduced the deviation from the baseline ΛCDM background) from considering two further elements: SNeIa, which are well known to play a complementary role with respect to BAO in fixing many cosmological parameters; and by applying a prior on H 0 from independent observations, given that present errors on H 0 are ∼ 2% [90], which is less than half the deviation from ΛCDM depicted in the same [13].…”
Section: B Gravitational Lensingcontrasting
confidence: 50%
“…Cosmological parameter analyses to test MG theories have been performed by several authors [340,884,895,896,903,[908][909][910][911][912][913]. Specific studies to determine the cosmological impact of galileon theories and to constrain model parameters appear in [265,[914][915][916][917][918][919][920].…”
Section: Cosmological Testsmentioning
confidence: 99%
“…However, no distant GW-EM event will possibly be observed if c g is modified significantly, since the delay between both signals will be much larger than the monitoring time around the GW detection. This is the case of cosmic acceleration models without a cosmological constant such as covariant Galileons [52,62], for which |c g /c − 1| ∼ 10 − 100% (see [57] and Fig. 1 of Ref.…”
mentioning
confidence: 99%